Single-incision laparoscopic versus conventional laparoscopic right colectomy: A systematic review and meta-analysis. (July 2018) - Dong, Boye; Luo, Zuyang; Lu, Jiabao; Yang, Yang; Song, Yixian; Cao, Jie; Li, Wanglin
Abstract: Background: Single-incision laparoscopic surgery has gained widespread attention because of its potential benefits such as less skin incision and faster recovery. Up to now, only one meta-analysis (performed in 2013; including 9 studies, a total of 585 cases) compared single-incision laparoscopic right colectomy (SILRC) with conventional laparoscopic right colectomy (CLRC). An updated meta-analysis was undertaken to explore more convinced comparative findings between SILRC and CLRC. Materials and methods: The search for studies that compared SILRC with CLRC was done on PubMed, Embase, Web of Science, and the Cochrane Library. A total of 17 studies (including 1778 cases) were identified, the data of appointed outcomes were extracted and analyzed. Results: Patient demographics (age, gender, body mass index and previous abdominal operation) did not differ significantly. No significant differences were found between SILRC and CLRC in operative time, conversion, reoperation, perioperative complications, postoperative mortality, and 30-days readmission. Pathological outcomes, including lymph nodes harvested, proximal resection margin, and distal resection margin, were similar. SILRC showed less estimated blood loss (weighted mean difference [WMD]: −15.67 ml; 95% confidence interval [CI], −24.36 to −6.98; p = 0.0004), less skin incisions (WMD: −1.56 cm; 95%CI, −2.63 to −0.49; p = 0.004) and shorter hospital stay (WMD: −0.73d; 95%CI, −1.04 to −0.41; p < 0.00001), without publication bias. Conclusion: SILRC may provide a safe and feasible alternative to CLRC with similar short-term outcomes and aesthetic advantage of less skin incision. Well-designed randomized controlled trials, involving large cases and carrying long-term outcomes, are needed. Highlights: SILRC showed similar short-term outcomes to CLRC. SILRC had less skin incision than CLRC. Randomized controlled trials are still needed to identify if SILRC is better.